Gender ambivalence (ambiguity?) - Deinert, Herbert (online, 2010)
The tentative title of my presentation is Gender ambivalence (ambiguity?) and deals with Renaissance iconography in Thomas Mann's Death in Venice. It will show that homosexual attraction, although obvious in the story (and Mann's life) is a secondary issue and that the main concern lies with the problem provided by an aesthetic principle. (Parallel narratives, the plot is not the real/only story)
urn:nbn:de:hebis:30-1147499